Degradation and early in vitro activity of healthy hepatocytes onto bicomponent electrospun fibers. Issue 16 (2nd November 2018) - Marrese, Marica; Guarino, Vincenzo; Fasolino, Ines; Cirillo, Valentina; Ambrosio, Luigi
ABSTRACT: Bicomponent electrospun fibers (BEFs) have been designed as building blocks of various biomedical devices, i.e., scaffolds, conduits, grafts, for the repair/regeneration of in vitro and in vivo tissues. With respect to monocomponent fibers, BEF may exert diversified patterns of signals—morphological, chemical or physical—confined at the single fiber level, conferring them a unique ability of self-adapting to local microenvironment and influencing cell/fiber interaction. Herein, an investigation of basic relationships between degradation properties of BEF and in vitro response of healthy hepatocytes to prove their use as in vitro model to predict in vivo liver regeneration is proposed. GRAPHICAL ABSTRACT: